'I'll take care of the flowers!' Researching agency through initiatives across different learning environments. Issue 1 (2nd January 2017) - Kangas, Marjaana; Kopisto, Kaisa; Löfman, Krista; Salo, Laura; Krokfors, Leena
ABSTRACT: This case study examined how the agency of a fifth-grade pupil appeared across different learning environments in the primary school context. In this study, agency is defined as the initiatives taken by an individual in interactive situations. The research question is: how does a pupil's agency manifest and vary through taking initiatives across different learning environments within curriculum-based education? The empirical data consist of 50 video episodes including learning activities in a classroom, in a vegetable garden and on a nearby farm. The findings show that the pupil's agency varied across learning environments, manifesting itself through complementing, supportive, constructive and challenging initiatives. When developing pedagogy that supports learning across formal and informal learning environments, it is essential to enable pupils to take different kinds of initiatives and to exercise their agency in versatile contexts.